Face-to-Face and Distance Education Modalities in the Training of Healthcare Professionals: A Quasi-Experimental Study - Souza, Carmem L. E.; Mattos, Luciana B.; Stein, Airton T.; Rosário, Pedro; Magalhães, Cleidilene R. (Frontiers in Psychology, 2018)
This study evaluates the effectiveness of an 18-month long course in Family Health. The course was offered in two modalities, distance education and face-to-face learning. Dependent variables were as follows: self-regulation of learning, procrastination, the perception of self-efficacy and academic performance. The course was attended by 27 health professionals (i.e. physicians, nurses and dentists) working in the Brazilian Unified Health System. The investigation followed a quasi-experimental design. Participants in the two modalities achieved similar academic performance; and globally no statistically significant differences were found regarding the study variables. Findings, notwithstanding their importance for professional training in health, are preliminary and further research is needed on the effectiveness of training modalities distance education and face-to-face learning (e.g. focus groups, interviews, online monitoring). The educational implications of this study are discussed and analyzed considering specificities and differences of each modality.